The effects of dissolved organic carbon on the reflex ventilatory responses of the neotropical teleost (Colossoma macropomum) to hypoxia or hypercapnia - Perry, Steve F.; Gilmour, Kathleen M.; Duarte, Rafael M. [UNESP]; Wood, Chris M.; Almeida-Val, Vera M.F.; Val, Adalberto L. (Elsevier, 2021)
The tambaqui (Colossoma macropomum), migrates annually between whitewater and blackwater rivers of the Amazon. Unlike the whitewater, blackwater is characterized by higher levels of dissolved organic carbon (DOC), including humic acids (HA). Because humic substances impair sensory processes, the current study tested the hypothesis that O2 and/or CO2 chemoreception is impeded in blackwater owing to the presence of HA. Thus, the ventilatory responses of tambaqui to hypoxia or hypercapnia were assessed in well water transported from Manaus, local blackwater, and in well water containing HA either extracted from Rio Negro water or obtained commercially (Sigma Aldrich; SA). In well water, tambaqui exhibited typical hyperventilatory responses to hypoxia or hypercapnia. These responses were prevented by simultaneously exposing fish to SA HA (20 mg l−1). The negative effects of SA HA on ventilation were prevented when natural DOC (30 mg l−1; extracted from Rio Negro water after first removing the endogenous HA fraction) was added concurrently, indicating a protective effect of this non-humic acid DOC fraction. The hyperventilatory responses were unaffected during acute exposure or after acclimation of fish to Rio Negro water. HA extracted from Rio Negro water did not impair the hyperventilatory responses to hypoxia or hypercapnia. This study, while demonstrating a negative effect of SA HA derived from peat (coal) on the control of breathing in tambaqui, failed to reveal any detrimental consequences of HA (derived from the decomposition of a variety of lignin-rich plants) naturally occurring in the blackwaters of the Rio Negro.
Keywords: Blackwater; Chemoreception; Control of breathing; Fish; Humic acids; Tambaqui (cachama)